The Impact of Fiscal Incentives on the Indonesian Recycling Industry: A General Equilibrium Analysis - Indri Riesfandiari; Imam Tri Wahyudi; Rama Bhaskara Praja (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The recycling industry plays a strategic role in supporting sustainable economic growth through waste reduction, increased resource efficiency, and job creation. Providing fiscal incentives, such as tax breaks, subsidies, or reduced import duties on environmentally friendly machinery/technology, is believed to be able to strengthen the competitiveness of the recycling industry. This study aims to assess the impact of fiscal incentive policies on the macro economy, including growth, income, and welfare distribution, using a Computable General Equilibrium simulation model. The main design of this study uses a quantitative approach with Computable General Equilibrium. The results show that fiscal incentive policies through bonded recycling zones have been proven to increase the competitiveness of the recycling industry by encouraging real household consumption, exports, and reducing raw material import costs. However, its positive impact on the national economy is still limited and poses challenges in the form of declining domestic demand for local raw materials and potential negative impacts on the informal sector. Therefore, the long-term success of the Bonded recycling zones policy requires regulatory refinements, more targeted incentives, and investment support in research and technology to strengthen the recycling industry and optimize the potential of the circular economy in Indonesia.